Efektivitas Program Ternak Babi Bergulir dalam Kesejahteraan Masyarakat di Desa Watu Lanur Kecamatan Lamba Leda Selatan Kabupaten Manggarai Timur Nusa Tenggara Timur - Amanda Nariswari; Khaerul Umam Noer (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The rolling pig farming program in Watu Lanur Village, NTT, is a women's empowerment initiative through dasawisma. This program aims to improve the economic and social welfare of dasawisma members by providing capital in the form of pig seeds which are maintained and developed on a rolling basis. Each group gets piglets to raise until they reach a certain age, then part of the results are returned to the program to be given to the next group. Data collection techniques use observation, interviews and documentation methods. The results of this research show that the effectiveness measurement indicator, namely understanding the program, can be said to be ineffective because there are still group members who do not understand when faced with problems such as pigs that are not fit and need treatment, are right on target, the implementation of the rolling pig farming program in Watu Lanur village is appropriate. with what is planned, starting from program planning, target groups, to planning strategies for successful implementation of the program, timely implementation of the Rolling Pig Farming Program cannot be measured with certainty because it is related to the reproduction of living creatures, Achieving the goal of implementing the rolling livestock program in Watu village The goal has not been achieved in accordance with the predetermined goals because not all groups have succeeded, this is due to the cold weather and the implementers or target recipients not having prepared for what will happen, and real change can be said to have not been effective because there are still many groups who fail.